Epidemiologia de afogamento: Estado e políticas públicas no Paraná - Schinda, Antonio (2013)
Drowning is a difficult problem to solve. Every year there are many deaths in the state of Paraná, the majority in isolated places. How can we reduce the number of drownings in the state of Parana? Where and how are the deaths by drowning occurring? What are the preventive measures that could be used as public policies for prevention? The main objective of the research was to analyze the drowning epidemiology in Paraná State to improve the understanding on this subject and also classify the problem of drowning deaths in liquid environment as one of the part of the social problem; it was also considered that social policies are actions from the State. Accordingly, therefore, the drowning epidemiology was treated and understood as a matter of public policy. As primary source, the occurrence records system from the Fire Department of Paraná (SISBM) was used to analyze the incidents of aquatic search, along with the analysis of the database about drowning used in the Unified Health System (SUS) called (DATASUS) in the period of 2008-2012, supplemented with official documents and reports, research reports, articles, books and the annals of the events. The research was divided as follows: in Section I a brief introduction was made on the origin of the subject of the research that was reported and the research problem; Section II approached the social and environmental characteristics of the drowning epidemiology and discussed some of the State and public policies; in Section III, the diagnoses was presented, social and environmental characteristics of the drowning epidemiology in Paraná using reports from DATASUL and SISBM; Section IV brought the data analysis, discussions, and final closing remarks